Streptococcal sagA activates a proinflammatory response in mast cells by a sublytic mechanism. (7th July 2019) - von Beek, Christopher; Waern, Ida; Eriksson, Jens; Melo, Fabio Rabelo; Robinson, Carl; Waller, Andrew S.; Sellin, Mikael E.; Guss, Bengt; Pejler, Gunnar
Abstract: Mast cells are implicated in the innate proinflammatory immune defence against bacterial insult, but the mechanisms through which mast cells respond to bacterial encounter are poorly defined. Here, we addressed this issue and show that mast cells respond vividly to wild type Streptococcus equi by up‐regulating a panel of proinflammatory genes and by secreting proinflammatory cytokines. However, this response was completely abrogated when the bacteria lacked expression of sagA, whereas the lack of a range of other potential virulence genes ( seeH, seeI, seeL, seeM, hasA, seM, aroB, pyrC, and recA ) had no effect on the amplitude of the mast cell responses. The sagA gene encodes streptolysin S, a lytic toxin, and we next showed that the wild type strain but not a sagA ‐deficient mutant induced lysis of mast cells. To investigate whether host cell membrane perturbation per se could play a role in the activation of the proinflammatory response, we evaluated the effects of detergent‐ and pneumolysin‐dependent lysis on mast cells. Indeed, exposure of mast cells to sublytic concentrations of all these agents resulted in cytokine responses of similar amplitudes as those caused by wild type streptococci. This suggests that sublytic membrane perturbation is sufficient to trigger full‐blown proinflammatory signalling in mast cells. Subsequent analysis showed that the p38 and Erk1/2 signalling pathways had central roles in the proinflammatory response of mast cells challenged by either sagA ‐expressing streptococci or detergent. Altogether, these findings suggest that sagA ‐dependent mast cell membrane perturbation is a mechanism capable of activating the innate immune response upon bacterial challenge.